Transformation of Principal's Academic Supervision Through Coaching to Improve Teacher Performance at SMP Negeri 10 Probolinggo - Agustyowati, Rini; Sunarni, Sunarni (Universitas Negeri Malang, 2024)
The study aimed to examine the transformation of academic supervision conducted by principals through coaching methods to improve teacher performance at SMP Negeri 10 Probolinggo. Academic supervision is crucial in ensuring the quality of teaching, and coaching, as a collaborative and reflective approach, offers an alternative to the more evaluative traditional supervision methods. With the implementation of coaching, principals can create a more supportive environment for teachers, to encourage professional development and reflection on teaching practices. This study used a qualitative approach with data collection through interviews, observations, and document analysis to explore how coaching is integrated in the academic supervision process and its impact on teacher performance. The findings show that coaching significantly increases teacher engagement, promotes reflective teaching practices and improves teacher performance in the classroom. The study also highlights the role of principals as facilitators in teachers' professional growth, suggesting that coaching- based supervision can be an important strategy in improving education quality.